Physiological foundations of load modeling in the annual training cycle of highly qualified canoe slalom athletes - Okun, D.; Korolova, M.; Stadnik, S.; Rozhkov, V.; Taran, L.; Mishyn, M.; Petrenko, I.; Tarasevic, O. (Journal of Physical Education and Sport, 2020)
The paper presents the results of a study of the volume and intensity of the load in the annual training cycle of the national team of Ukraine in canoe slalom.The interest in building a one-year training cycle in various sports always remains in the center of attention of specialists, since it is the one-year planning of the training process that is the culmination of all the trainer's creative work, embodied in a specific document, on the basis of which all other training cycles, individual classes and motor tasks are detailed. Purpose of the study is to determine the optimal volume and intensity of training loads in building the training process of the national team of Ukraine in canoe slalom.In the course of the study, it was revealed that the total rowing volume in various intensity zones was on average 5115.26 ± 283.49 km (100%). As for the ratio of volumes in different zones of muscle work intensity, the rowing volume in the zone of moderate power averaged 2383.36 ± 142.74 km. With such rowing intensity, when the concentration of lactate does not exceed 2 mmol / l, the energy supply of muscle activity, that is, physical work, is carried out exclusively due to the aerobic mechanism. Under such conditions, the heart rate (HR) of athletes is within 70-80% of the maximum, and the intensity of the training load corresponds to 80-90% of the level of the anaerobic threshold (ANT). It should be noted that the share of rowing in this power zone is quite large and averages 46.6% of the total rowing volume. It is established that the total mileage of rowing on the water is on average 5115 km.Of these: rowing in the moderate power zone - 2383 km (46.6%); rowing in the submaximal power zone - 2419 km (47.1%); rowing in the zone of high power - 229 km (4.5%); rowing in the zone of maximum power - 92 km (1.8%). The created model of the volume and intensity of training loads can be considered basic in the construction of the training process of highly qualified rowers.